Identidades e línguas de sujeitos diversificados em discursos de políticas públicas dos povos originários - Cândido, Amanda Gomide de Sousa (2020)
In this work we tried to point out a theoretical horizon covering Applied Linguistics (LA) points of view and Discourse Analysis (AD) presuppositions to debate about indigenous national supposed representation and identity, indigenous school education and linguistic sovereignty. Thus, the objective is to study issues involved in the lack of definition of a current national indigenous identity, within Applied Linguistics, in order to highlight the translation of opposing positions that discuss the identity of native people, differentiated indigenous education and their linguistic rights. In this analysis, it was selected a documentary corpus divided into two main lines: 1 - statements that defend the diversity and freedom of the indigenous people to own land, have the right to be and be everywhere, assume different social positions, have any phenotype and present themselves with different styles. Beyond this, being able to have a heterogeneous way of life with practices similar to other Brazilians, without necessarily have their identity neutralized or weakened; 2 - other statements that problematize and refute the idea of a person identified as indigenous and who is inserted in urban environments, having cohesive practices with the globalized world, who is cult, in other words, that escapes a stereotype crystallized for centuries and who, at the at the same time, demands for differentiated education and health, validation and valuation of traditional knowledges and cultures which are far from hegemony, and, perhaps mainly who demands demarcation of indigenous lands (TI) and expansion of demarcated lands. When evidencing the process of translating statements from divergent discursive fields, it was possible to perceive that the debates and confrontations of understandings at first, about indigenous school education and, also considering, the speeches about identity and indigenous representation began to appear as “arguments” and “Pretexts” for a deeper debate on territorial, economic, cultural and linguistic sovereignty. With the selection of statements present in this discursive universe, this study intends to reflect on the influence of language in the production of social vulnerability and limitation of possibilities in the daily lives of the subjects involved. There is a controversy - radical antagonism - around issues of identity, property, productivity and land use for the traditional subsistence practices of the contemporary Brazilian autochthone. In this sphere of conflicts, agrarian conflicts bring alarming numbers of deaths, and for this reason they are examples of the extreme violence arising from the competition of ideas. Bearing this in mind, we can see the urgency and outcry of the claims of the speeches involved, and also why this incompatibility must be widely debated in the search for solutions that protect these vulnerable groups, since the disagreement will invariably occur. So, researching this situation seems pertinent to me to highlight the complexities of situations without simple solutions.